Computational fluid dynamics simulations and experimental validation of tracer gas distribution in an experimental underground mine - Xu, Guang; Bowling, J.; Luxbacher, K.; Ragab, S. (2011)
Following a disaster in a mine, it is important to understand the state of the mine damage immediately with limited information. Computational fluid dynamics can be used to simulate and ascertain information about the state of ventilation controls inside a mine. This paper describes a simulation of tracer gas distribution in an experimental mine with the ventilation controls in various states. Tracer gas measurements were taken in the lab experimental apparatus, and used to validate the numerical model. The distribution of the tracer gas, together with the ventilation status, was analyzed to understand how the damage to the ventilation system related to the distribution of tracer gases. This study will be used in future research in real mine measurements to compare collected and simulated profiles and determine whether damage to the ventilation system has been incurred during an emergency situation, the nature of the damage and the general location of the damage.